2021
DOI: 10.1016/j.jviromet.2021.114249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low-cost viral concentration methods in wastewaters: Implications for SARS-CoV-2 pandemic surveillances

Abstract: In the pandemic of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) many strategies have been performed in order to control viral spread in the population and known the real-time situation about the number of infected persons. In this sense, Wastewater Based Epidemiology (WBE) has been applied as an excellent tool to evaluate the virus circulation in a population. In order to obtain reliable results, three low-cost viral concentration methods were evaluated in this study, polyethylene glycol (PEG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Additionally, the clinical respiratory tract infections show similarities [30]. Because of all these resemblances, BCoV has already been suggested and successfully employed as a SARS-CoV(-2) surrogate in many different applications [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the clinical respiratory tract infections show similarities [30]. Because of all these resemblances, BCoV has already been suggested and successfully employed as a SARS-CoV(-2) surrogate in many different applications [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…As a control of the viral concentration process, 100 μL and 50 μL of PP7 bacteriophage (1.0 × 10 6 genomic copies/μL) were added to 10 L of surface water and 500 ml of wastewater samples, respectively. Wastewater samples were concentrated with PEG precipitation method, according to the protocol described by Lewis and Metcalf ( 1988 ) with modifications (Salvo et al, 2021 ). Briefly, weights of centrifugation pots were registered, 500 ml of sample was distributed in two bottles (250 ml each) and centrifuged at 4750 xg for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The PEG concentration efficiencies in this study were 82.7% and 50.3% with geometric standard deviations 1.7 and 2.1 for PEG-DC and PEG-QVR, respectively, showing relatively stable and high performances. Previous studies have shown that the virus concentration rates from wastewater treated with PEG were as low as less than 10% in some cases (Salvo et al 2021, Philo et al, 2021, Barril et al 2021). In addition, there is no unified or standardized method for the concentration of the is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Efficacy Of Virus Detection Processmentioning
confidence: 97%
“…The concentration efficiency was thought to vary significantly with the reported cases and workers. Therefore, although virus concentration by the PEG was a relatively low-cost method and has been applied in many studies (Salvo et al, 2021, LaTurner et al, 2021, in practice, it was necessary to select the optimized conditions depending on the target virus and the condition of the wastewater sample.…”
Section: Efficacy Of Virus Detection Processmentioning
confidence: 99%
See 1 more Smart Citation